An Analysis of Speech Acts in Margaret Ogola's the River and the Source and I Swear by Apollo - Oloo, Nicholas Onyango (JOOUST, 2019)
Novels are characterized by narration. However, in some instances depending on the style of the author, some portions of the novel may consist of interactions between the characters. It is therefore through speech acts analysis that the reader can interrogate how the writer develops the plot, characterization and the major concerns in the novel through discourse situations where a character talks to another character. This study examined speech acts in Margaret Ogola's two novels' The River and the Source (1994) and I Swear by Apollo (2002).In this regard, the objectives of this study were, firstly, to interrogate the significance of speech acts in comprehending dialogue in the novels The River and the Source and I Swear by Apollo, secondly, to describe the types of speech acts used by the writer in the novels The River and the Source and I Swear by Apollo, and finally to evaluate the uses and significance of speech acts used in the novels The River and the Source and I Swear by Apollo. Austin's (1962) Speech Act Theory guided this study. The study employed an analytical research design. A mixed method approach was used to analyze the data. Qualitative method was used to present the data in form of description whereas quantitative was used to count the total number of the speech acts used by the main characters. The population in this study was all the four novels by Ogola. To achieve its objectives; the study purposively selected two of her four novels due to the extensive use of dialogue in these two novels. Library research and content analysis were used in collecting data. Data was obtained from reading and analysis of the primary texts supplemented by secondary texts. The data was in form of utterances from the characters' conversations containing speech acts. The study concluded that speech acts in pragmatics could be used in the analysis of characters' utterances in the novels in the same way as daily verbal interactions. Secondly, the findings indicated that every utterance used by a character performs three simultaneous acts, namely: a locutionary, an illocutionary and perlocutionary. Moreover, every utterance produced by a character in the novels could be categorized under one of the five major categories of speech acts proposed by Searle: representatives, expressives, directives, commissives or declarations. The study found that all these five major speech acts were used by the writer in the novels with the representative being the most dominant in both novels and the declarations the least. In addition, the successful performance of each speech act depends on satisfying the four linguistic and non linguistic conditions called felicity conditions which interlocutors use in production and interpretation of utterances. These are the propositional, preparatory, sincerity and essential conditions. The study also revealed that each major speech act contains a wide range of sub acts or illocutionary forces which are distinguished based on their felicity conditions. For this reason, the findings showed that the writer used thirty six sub acts in the novels with the act of asserting having the highest frequency. Finally, the study also found out that both direct and indirect speech acts are used in the novels with the direct speech acts having the highest frequency of use. This study recommends that a speech act analysis be adopted as an effective tool in the analysis of the characters' verbal interactions in novels. In addition, it recommends that further research be conducted on speech act analysis of novels by other writers.